Meeting Technologies and Optimal Trading Mechanisms in Competitive Search Markets - Benjamin R. Lester; Ludo Visschers; Ronald P. Wolthoff (Institute for the Study of Labor (IZA), 2014)
In a market in which sellers compete by posting mechanisms, we study how the properties of the meeting technology affect the mechanism that sellers select. In general, sellers have incentive to use mechanisms that are socially efficient. In our environment, sellers achieve this by posting an auction with a reserve price equal to their own valuation, along with a transfer that is paid by (or to) all buyers with whom the seller meets. However, we define a novel condition on meeting technologies, which we call "invariance," and show that the transfer is equal to zero if and only if the meeting technology satisfies this condition.
Keywords: C78; D44; D83; 330; search frictions; matching function; meeting technology; competing mechanisms